Development and Validation of Women’s Empowerment in Migration Index (WEMI) - Sufian, Farha D.; Alvi, Muzna; Ratna, Nazmun N.; Ringler, Claudia; Choudhury, Zahid ul Arefin (International Food Policy Research Institute, 2023)
There is little evidence on the association between women’s migration, empowerment, and well-being, driven in part due to difficulty in measuring empowerment in the migration context. To better understand these linkages, we developed a Women’s Empowerment in Migration Index (WEMI) and validated it with survey of 1019 returnee female migrants in Bangladesh, who had returned after working internationally, mostly from countries in West Asia. By incorporating indicators of subjective well-being from migration literature into measures of empowerment, our paper advances research over earlier assessments of women’s experiences in the migration process beyond seemingly objective indicators, such as income, health, and economic welfare. We find that 14% of all migrant women in our sample could be classified as being empowered. Lack of membership in groups, restricted mobility, and lack of asset ownership are the largest contributors to migrant women’s disempowerment in our sample. We find that WEMI is strongly correlated with other measures of well-being, including mental health and livelihood-efficacy. Women with higher empowerment scores are also less likely to experience discriminatory labor practices and unsafe work conditions. With broad applicability to migrants from low and middle-income countries, WEMI can be used as a tool, helping to identify sources of disempowerment, and enabling stakeholders to develop interventions targeting the welfare of women migrant workers.